Effect of Solvent on Structure and Optical Properties of PZT Nanoparticles Prepared by Sol-Gel Method, in Infrared Region - Zak, A.K.; Abd Majid, Wan Haliza (2011)
Single-phase perovskite Pb(Zr(0.52),Ti(0.48)) nanoparticles, PZT-NPs were prepared by the sol gel method with two different solvents, 2-methoxyethanol, EGME, and poly ethylene glycol, PEG. X-ray diffraction (XRD) was used to study of the structure of the PZT-NPs. Fourier transform infrared spectroscopy (FTIR) was used to measure the infrared reflectivity spectrum in the range of 4000-280 cm(-1). Infrared active vibration modes of BO(6) octahedral (nu(1) and nu(2)) were observed for PZT-NPs below 600 cm(-1). The third vibration mode of Pb against the TiO(3) group, nu(3), occurred below the experimentally accessible range. The Kramers-Kronig method (K-K) and classical dispersion theory were applied to analyze the data and calculation of the optical constants such as reflective index (N(omega))and permittivity (epsilon(omega)). The results showed that the structure and optical properties of PZT-NPs were changed by different type of solvent. (C) 2010 Elsevier Ltd and Techna Group S.r.l. All rights reserved.